MoO2@Cu@C Composites Prepared by Using Polyoxometalates@Metal-Organic Frameworks as Template for All-Solid-State Flexible Supercapacitor. (10th January 2016) - Zhang, Yidong; Lin, Baoping; Sun, Ying; Han, Pei; Wang, Junchuan; Ding, Xiaojing; Zhang, Xueqin; Yang, Hong
Graphical abstract: Abstract: We have synthesized a composite of MoO2 @Cu@CusingathermolysistemplateofPOM@MOFcrystal(POM = polyoxometalates, MOF = Metal–organic frameworks), in which the Keggin-type Mo-based POMs with negative charges exist as secondary building units of Cu-based MOF. In addition, the material is confirmed to exhibit an excellent capacity of 28.33 mAh g −1 at a current density of 1 A g −1, which is much higher than MoO2 -based supercapacitors reported before. Moreover, we have fabricated a symmetrical flexible all-solid-state device with the MoO2 @Cu@C electrode using PVA-KOH gel polymer as electrolyte and separator, and it shows outstanding sTable performance retaining 91% of its highest charge capacity maintained after 5000 cycles. The present study displayed a novel thermolysis template in the term of POM@MOF and provided an accessible foundation for investigations of MoO2 -based supercapacitors.